MICRO SMALL ENTERPRISES’ INTEREST IN ISLAMIC FINANCING: CASE OF MSEs AND ISLAMICS BANKS IN YOGYAKARTA - Khusnul Hidayah; Wahyudin Wahyudin (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2019)
The development of the micro and small enterprises (MSEs) in Yogyakarta City grew rapidly and was able to support the economic sector of the city. Nevertheless, they usually face some problems related to limited capital, market access and product quality. Islamic banking is expected to play a role in overcoming such problems, especially in providing capital to improve the product quality and market access. This study aims to acquire the empirical evidence of the effect of profit sharing, personal, and service factors on the MSEs’ interest in Islamic financing provided by Islamic banks in Yogyakarta City.This study employed a survey method using a research questionnaire distributed to MSE entrepreneurs in Yogyakarta City. The source of data was primary data and the data was analyzed using SPSS software. Of the total 70 distributed questionnaires, only 60 were responded and collected by the respondents. The data analysis techniques included data quality testing, classical assumption test, and hypothesis testing (Multiple Regression Analysis, Coefficient of Determination, F-Test, and T-Test).The results showed that profit sharing, personal factors, and service influence the MSEs’ interestin Islamic bank products provided by Islamic Banks in Yogyakarta City.